Problems of the actual application of international humanitarian law to cyber attacks in contemporary armed conflicts . - صفطلي مايا (Latakia University Journal - Economic and Legal Sciences Series, 2024)
In recent years, the dilemma of using the Internet or computers as a tool of modern warfare has emerged, and it has become common to raid and destroy websites remotely to detonate their contents. For example, it is possible to close the centrifuges of nuclear facilities, disable air defense systems, air traffic control systems, and oil and gas pipeline flow system, open damgates, or control electrical networks, water facilities, communication, transportation, and other facilities that affect national security or the national economy or the supreme interest of the state. Thus, it represent and disruption at the international level accordingly, disagreement arises and the international legal and jurisprudential debate is currently escalating regarding cyber attacks launched during contemporary international or non- international armed conflicts. Especially regarding the actual and real application of the most important rules and principles applicable in international humanitarian law to these attacks, because the targets in any cyber conflicts will be civilians, not military, and will effect the civilians population and civilians objects and will not be limited to military forces and targets only .